ATTACK KEY AES ON NOTDUINO USING POWER ANALYSIS CORRELATION - Rahman Nuradha, Faisal
Encryption is a technology that works by scrambling data so that it cannot be read by unwanted parties. The Advanced Encryption Standard (AES), also known as Rijndael, is a specification for electronic data encryption The tool used in the implementation of AES is ATmega328p. ATmega328P is an 8-bit AVR CMOS based microcontroller with RISC architecture. Correlation Power Analysis (CPA) is an attack that allows us to find the secret encryption key stored on a hardware device (Hadware). Notduino is a device that is used as a target for the ChipWisperer Capture system. With this notduino, the writer can do attack activities to get the AES key used on the microcontroller. The researcher used the CW1173 board to retrieve the trace when the AES program worked. With CPA analysis with the Hamming distance Sbox output method the researcher managed to find all the subkey keys used in the AES encryption algorithm. With the results obtained, it shows that higher security is needed for AES encryption so that it is not easy to attack.